Determinants of Financial Well-being: The Moderating Role of Internal Locus of Control - Dina Aulia Agustiani; Rahmadani Nur Permanawati (STKIP Singkawang, 2026)
This study aims to analyze the influence of financial literacy, financial stress, and financial behavior on financial well-being, with internal locus of control as a moderating variable, among workers in Semarang City. A quantitative method was used, employing purposive sampling of 135 respondents with incomes at or below the regional minimum wage. Data analysis was conducted using Partial Least Squares-Structural Equation Modelling (PLS-SEM). The results indicate that financial literacy and internal locus of control have a positive and significant effect on financial well-being. Conversely, financial stress, financial behavior, and all moderation effects were found to be insignificant. Based on the study’s findings, it is recommended that workers enhance their comprehensive financial literacy and self-control. Meanwhile, future researchers are advised to explore macro-level factors beyond the psychological model to address the limitations of this study.